A call on Art investments - Roman Kraeussl; Christian Wiehenkamp (Goethe University Frankfurt, Center for Financial Studies (CFS), 2010)
The art market has seen boom and bust during the last years and, despite the downturn, has received more attention from investors given the low interest environment following the financial crisis. However, participation has been reserved for a few investors and the hedging of exposures remains dificult. This paper proposes to overcome these problems by introducing a call option on an art index, derived from one of the most comprehensive data sets of art market transactions. The option allows investors to optimize their exposure to art. For pricing purposes, non-tradability of the art index is acknowledged and option prices are derived in an equilibrium setting as well as by replication arguments. In the former, option prices depend on the attractiveness of gaining exposure to a previously non-traded risk. This setting further overcomes the problem of art market exposures being dificult to hedge. Results in the replication case are primarily driven by the ability to reduce residual hedging risk. Even if this is not entirely possible, the replication approach serves as pricing benchmark for investors who are significantly exposed to art and try to hedge their art exposure by selling a derivative.
urn:nbn:de:hebis:30-75143
Keywords: G11; G13; Z11; 330; Art Market; Art Index; Alternative Investments; Option Pricing; Kunst; Markt; Index; Kapitalanlage; Optionsgeschäft; Optionspreistheorie; Hedging; Theorie; Welt